Identification and characterisation of colour-changing marine bacteria isolated from seaweed - Quek, Aloysius Jun Hui (Nanyang Technological University, 2023)
Bacteria are ubiquitous in the marine environment. They play an important role in the regulation of Earth’s biogeochemical cycles and exist in tight interkingdom partnerships with many higher organisms, particularly with marine macroalgae that feed marine coastal communities. Often, these surface-associated bacteria are responsible for providing a wide range of beneficial functions to their macroalgal host, such as promoting and maintaining healthy growth of the macroalga. Most importantly, a wide range of bioactive secondary metabolites with diverse pharmacological and industrial properties have been reported to be produced by these epiphytic bacterial communities, highlighting the potential of phycospheric habitats as a rich source of novel natural compounds. From bioprospecting, a unique colour-changing bacteria B116 was isolated from Sargassum ilicifolium. Through a series of cultivation and molecular-based experiments, it was revealed that the B116 isolate was a strain of Pseudoalteromonas, capable of producing both red and green pigments. Preliminary data suggest that the red pigment is prodigiosin, a known compound with antimicrobial, antifungal and algicidal activities. As the mechanism behind the dual pigmentation of this novel Pseudoalteromonas sp. remains to be elucidated, further experiments investigating the regulation and expression of both pigments at the transcriptomic level are recommended.